Conceptualizing ‘quality of education’: an analysis of European political documents on education - Figueiredo, Carla (Frontiers in Education, 2025)
This paper conceptualizes ‘quality of education’ in the European political discourse. The expression ‘education quality’ and its variations are frequently found in literature and policies at supranational, international, national, and local levels but are not explicitly defined. However, it is assumed to be a goal that countries pursue and has gained prominence in the European context. Acknowledging the European agencies’ legislation’s influence on Member-States’ domestic policies, understanding what “education quality” means is of the utmost importance. Based on the content analysis of political documents issued by several European agencies, this paper categorizes, systematizes, and interprets the European political discourse on education to infer aspects that can compose ‘quality of education’ and develop an understanding of the concept. The analysis resulted in the systematization of three aspects that help to conceptualize the ‘quality’ of education: (i) ‘What is expected of education’; (ii) ‘Components of education quality’; (iii) ‘Priorities for Education’. Based on these aspects, a generic definition was formulated stating that education of quality is oriented toward preparing people to contribute to the social and political project, acquiring knowledge, skills, and competences to be productive; needing motivated and well-prepared teachers and leaders, adequate conditions, and being closely monitored and evaluated. The paper concludes with some recommendations. The paper conclusions could help policy-makers and school professionals in their professional practice and reaching education quality. Nonetheless, by only focusing on European documents addressing ‘quality of education’ the paper may present a narrower perspective that could be complemented by analyzing a wider range of international/transnational documents.